Toward Affirming Care: An Initial Evaluation of a Sexual Violence Treatment Network's Capacity for Addressing the Needs of Trans Sexual Assault Survivors. Issue 21 (November 2021) - Du Mont, Janice; Kosa, Sarah D.; Abavi, Rebecca; Kia, Hannah; Macdonald, Sheila
There is a global call to action to improve transgender (trans) health to achieve health equity for people of all gender identities. Trans persons experience high rates of sexual assault and have historically had limited or no access to health care that meets their needs. As an initial step in addressing this, we evaluated a sexual assault treatment network's capacity for addressing the needs of trans sexual assault survivors. Working with an Advisory Group comprising trans community members and their allies who have expertise in trans health, a short online questionnaire was developed and distributed to the program leaders of Ontario's 35 hospital-based Sexual Assault/Domestic Violence Centres (SA/DVTCs). A total of 27 program leaders completed the questionnaire for a response rate of 77%. The majority of respondents reported that their program collaborates with trans-positive services within their community (70.4%). However, only two in five (40.7%) program leaders indicated that the patient bill of rights at their hospital included a statement pledging nondiscrimination on the basis of gender, gender identity, and/or gender expression. All (100%) program leaders felt that the nurses and physicians working within their programs would benefit from (further) training in the care of trans persons who have been sexually assaulted. This study represents an important step in a research program aimed at enhancing Ontario SA/DVTCs' response to trans persons.